Atividades biológicas, isolamento de compostos ativos e caracterização de extratos obtidos de Scutia Buxifolia Reissek. - Boligon, Aline Augusti (2014)
Scutia buxifolia Reissek belongs to the Rhamnaceae family and is popularly known as coronilha. The stem bark infusion is popularly used as cardiotonic, antihypertensive and diuretic. This work aims to determine the antimicrobial and antiviral activities and antiulcer capacity and the toxicity of S. buxifolia against Apis mellifera adults, as well as identify and extract the essential oil components, characterize the utilized extracts and fractions and isolate chemicals constituints. Stem bark and leaves of S. buxifolia were collected in the city of October 2007 in Dom Pedrito-RS (coordinates 30º 59'09''S and 54º27'44''W). The material is deposited in the herbarium of the Department of Biology UFSM cataloged under the registration number SMBD 10919. The dried plant material was ground and macerated using ethanol: water (70:30, v/v) as solvent. The crude extract was fractionated with solvents of increasing polarity (dichloromethane, ethyl acetate, n-butanol). Ethyl acetate and n-butanol fractions showed the best antimicrobial and antiviral activities. The crude extract of S. buxifolia (100, 200 and 400 mg/kg) reversed the gastric damage caused by ethanol in the stomach of rats in a dose-dependent manner. Moreover, the species showed no toxicity against Apis mellifera after 15 days of observation. The main components identified in the essential oil were spathulenol, β-cubebene, germacrene D and carvacrol. Phenolic acids (gallic, chlorogenic and caffeic acids) and flavonoids (rutin, quercetin, isoquercitrin, quercitrin and kaempferol) were the main compounds identified and quantified in the crude extract and fractions of S. buxifolia. Finally, sitosterol-3-O-β-D-glucoside, β-sitosterol and ursolic acid were isolated from the dichloromethane fraction of the species. Our results indicated that S. buxifolia have a beneficial role in the treatment and prevention of certain diseases, and the chemical compounds present in the species contribute to the properties found.